Prevalence of Common Gynecological Conditions in the Middle East: Systematic Review and Meta-Analysis - Mousa, Mira; Al-Jefout, Moamar; Alsafar, Habiba; Kirtley, Shona; Lindgren, Cecilia M.; Missmer, Stacey A.; Becker, Christian M.; Zondervan, Krina T.; Rahmioglu, Nilufer (Frontiers in Reproductive Health, 2021)
Introduction: High prevalence of gynecological conditions in women of Middle Eastern origin is reported, likely due to regional risk-factors and mediators. The objective of this systematic-review and meta-analysis is to investigate the prevalence of polycystic ovary syndrome (PCOS), endometriosis, uterine fibroids and adenomyosis in women of Middle Eastern origin. Methods: MEDLINE, EMBASE, PsycINFO, Global Health and Google Scholar databases were searched from database inception until 14 February 2021 to identify relevant studies. Peer-reviewed research articles that reported the prevalence of PCOS, endometriosis, uterine fibroids and adenomyosis in the Middle Eastern population, written in English or Arabic. The primary outcome was the estimated pooled prevalence of PCOS, endometriosis, uterine fibroids and adenomyosis in the Middle Eastern populations. The secondary outcome was to assess the evidence in the data for the presence of heterogeneity, by conducting subtype pooled-analysis of prevalence estimates of the conditions. Total weighted prevalence was calculated via Freeman-Tukey-arcsine-transformation and heterogeneity through I2-statistic. Quality-control was performed using GRADE criteria. Results: A total of 47 studies, 26 on PCOS, 12 on endometriosis, 8 on uterine fibroids and 7 on adenomyosis, were included. The pooled-prevalence of PCOS diagnosed according to the NIH-criteria was 8.9% (95%CI:6.5-11.7; prevalence-range:4.0-27.6%), with a higher prevalence from the Gulf Arab states (18.8%, 95%CI:9.5-30.3; range:12.1-27.6%). According to the Rotterdam-criteria, the pooled prevalence of PCOS was 11.9% (95%CI:7.1-17.7; range:3.4-19.9%) with studies limited to the Persian and Levant regions. Endometriosis was diagnosed in 12.9% (95%CI:4.2-25.4; range:4.2-21.0%) of women undergoing laparoscopy, for any indication. Uterine fibroids and adenomyosis prevalence of women was 30.6% (95%CI:24.9-36.7; range:18.5-42.6%) and 30.8% (95%CI:27.1–34.6, range:25.6-37.7%), respectively. Heterogeneity was present between studies due to statistical and methodological inconsistencies between studies, and quality of evidence was low due to sample size and unrepresentative participant selection. Conclusion: This is the first review that has reported the prevalence of gynecological diseases in the Middle Eastern population, suggesting that gynecological morbidity is a public health concern. Due to the health disparities in women, further research is required to understand the relative roles of environmental and genetic factors in the region to serve as a benchmark for evaluation and comparative purposes with other populations.